Structural Analysis of Chassis Frame of a Prototype Car: A Finite Element Method - Ahmad Khairul Faizin; Ryan Rizaldi; Wahyu Aditya Setya Putra; Nailul Hasan (Nusantara Science and Technology Proceedings, 2023)
Cars are a means of transportation that is considered very important in human life, so it requires a high level of safety and comfort. Currently, there has been a lot of research on the manufacture of prototype category energy-efficient car chassis with electric motor drive. The frame is an integral part and an important part in the design of a vehicle. The frame was design using software with frame dimensions of 2.230 mm long and 360 mm wide. The material used is 7075 aluminum prototype chassis. Furthermore, the chassis frame construction was evaluate using the static simulations in order to determine von misses stress, displacement, and safety factor. The analysis carried out with a maximum load of 1.000 N, the results of the von misses stress analysis were obtained with the highest stress level of 13.8 MPa. The maximum displacement result is 0.39 mm was in the driver position, with a maximum safety factor of 3 and a minimum of 1, it is declared safe.